Clinical and Genetic Factors to Inform Reducing Colorectal Cancer Disparitites in African Americans - Carethers, John M. (Frontiers in Oncology, 2018)
Colorectal cancer (CRC) is the third most prevalent and second deadliest cancer in the U.S. with 140,250 cases and 50,630 deaths for 2018. Prevention of CRC through screening is effective. Among categorized races in the U.S., African Americans (AAs) show the highest incidence and death rates per 100,000 when compared to Non-Hispanic Whites (NHWs), American Indian/Alaskan Natives, Hispanics, and Asian/Pacific Islanders, with an overall AA:NHW ratio of 1.13 for incidence and 1.32 for mortality (2010-2014, seer.cancer.gov). The disparity for CRC incidence and worsened mortality among AAs is likely multifactorial and includes environmental (e.g. diet and intestinal microbiome composition, prevalence of obesity, use of aspirin, alcohol and tobacco use), societal (e.g. socioeconomic status, insurance and access to care, and screening uptake and behaviors), and genetic (e.g. somatic driver mutations, race-specific variants in genes, and inflammation and immunological factors). Some of these parameters have been investigated, and interventions that address specific parameters have proven to be effective in lowering the disparity. For instance, there is strong evidence raising screening utilization rates among AAs to that of NHWs reduces CRC incidence to that of NHWs. Reducing the age to commence CRC screening in AA patients may further address incidence disparity, due to the earlier age onset of CRC. Identified genetic and epigenetic changes such as reduced MLH1 hypermethylation frequency, presence of inflammation-associated microsatellite alterations, and unique driver gene mutations (FLCN and EPHA6) among AA CRCs will afford more precise approaches towards CRC care, including the use of 5-fluorouracil and anti-PD-1.